RESEARCH OF ALISHER NAVOI DEVONS IN THE FIELD OF TEXTUAL STUDIES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article deals with the “Ilk devon” (First Devonian) compiled by the admirers of Alisher Navoi, the official devons ordered by the poet himself: the devons “Badoyi’ ul-bidoya” and “Navadir un-nihoya”, their manuscript copies, issues of study in the second half of the 20th century.